The Consequences of the Growth of Health Insurance Premiums - Baicker, Katherine; Chandra, Amitabh (American Economic Review, 2005)
In the United States, two-thirds of the nonelderly population is covered by employerprovided health insurance (EHI). According to a Kaiser Family Foundation national survey (2003), the cost of EHI has increased by over 59 percent since 2000 with no accompanying increase in the scale or scope of benefits. These increases in health insurance premiums may have significant effects on labor markets, including changes in the number of jobs, hours worked per employee, wages, and compensation packages. Indeed, it is possible that a significant portion of the increase in the uninsured population may be a consequence of employers shedding this benefit as health insurance premiums rise. Understanding how labor-market characteristics affect adjustments to increased health insurance costs is of vital policy importance. Some proposals to cover the uninsured rely on “employer mandates” requiring employers to cover eligible workers. Other proposals provide tax credits for the purchase of non-employer health insurance. The effects of these proposals on employment, wages, and health insurance coverage will be driven by the elasticities of labor supply and demand, institutional constraints on wages and compensation packages, and how much workers value the increase in health insurance costs. Since employers provide such coverage voluntarily, if workers fully value these benefits and are able to sort between firms based on their preferences, then (in the absence of other institutional constraints) they will bear the cost of the increase via reduced wages, with no accompanying change in employment, employment costs, or employee utility. There are many reasons to believe, however, that firms are limited in their ability to offset increases in the price of health insurance premiums through lower compensation, so that increases in the cost of providing health insurance may affect both employment and the structure of work. Identifying the magnitude of these effects empirically is difficult both because of data availability and because of multiple avenues for causality. In this paper we uncover the causal effect of increases in the cost of benefits on labor-market outcomes by exploiting an exogenous source of variation in the cost of providing health insurance: the recent “medical malpractice crisis” in which malpractice costs for physicians grew dramatically in some states but not in others. The growth in malpractice payments affects malpractice insurance premiums and health insurance premiums, but it should not affect other aspects of employment (see Baicker and Chandra, 2005b). Using this source of variation, we examine the effect of increases in health insurance premiums on employment patterns, earnings, and health insurance coverage. We find that the cost of increases in health insurance premiums is borne in large part by workers through increased unemployment and also through decreased hours for those workers moved from full-time jobs with benefits to parttime jobs without. These results have strong implications for the distributional impact of health-care reforms. * Both authors: Economics Department, Dartmouth College, 6106 Rockefeller Hall, Hanover, NH 03755, Dartmouth Medical School, and National Bureau of Economic Research (e-mails: kbaicker@dartmouth.edu, achandra@ dartmouth.edu). We thank Alan Garber, Seth Seabury, Jonathan Skinner, and Douglas Staiger for helpful conversations that have influenced this research program, and Derek Neal, Aaron Yelowitz, and conference participants at the Berger Conference for very insightful comments. We are grateful for funding from NIA-P01 AG19783-02. The opinions in this paper are those of the authors and should not be attributed to the NIA or NBER. 1 Based on tabulations of population under age 65 from the March Current Population Survey for 1988–2003. 2 There is a wide literature estimating the wage–fringe trade-off. A $1 increase in the value of fringes may be offset by a $1 reduction in wages—or a $1/(1 tax rate) reduction for tax-favored benefits. For example, Jonathan Gruber (1994) demonstrates that the passage of the Pregnancy Discrimination Act in 1978 resulted in employers shifting the entire cost of the mandate onto employees.